1993
DOI: 10.1042/bj2890829
|View full text |Cite
|
Sign up to set email alerts
|

Fulvic acid supplementation and selenium deficiency disturb the structural integrity of mouse skeletal tissue. An animal model to study the molecular defects of Kashin-Beck disease

Abstract: High concentrations of fulvic acid and selenium deficiency are the main causative factors of Kashin-Beck disease, an endemic, chronic and degenerative osteoarticular disorder found in China. In the search for an animal model of this disease, mice were exposed to these pathogenetic conditions for two generations and the collagen types from skin, bone and cartilage were analysed. The growth of the treated mice was slightly retarded, and the rate of reproduction was lower in animals maintained on a fulvic acid-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 19 publications
2
33
0
1
Order By: Relevance
“…To this point, as also suggested by the literature (14)(15)(16)(17), it is worth noting that a changed matrix is certainly relevant to the biological features of bone. Although the main difference between trabecular and cortical bone is the much greater surface area of the former, which explains the differences in bone turnover rates between cortical and trabecular bone, the hypothesis that a modified and possibly defective matrix could somehow be recognized and further removed by osteoclasts cannot be excluded.…”
Section: Discussionmentioning
confidence: 90%
“…To this point, as also suggested by the literature (14)(15)(16)(17), it is worth noting that a changed matrix is certainly relevant to the biological features of bone. Although the main difference between trabecular and cortical bone is the much greater surface area of the former, which explains the differences in bone turnover rates between cortical and trabecular bone, the hypothesis that a modified and possibly defective matrix could somehow be recognized and further removed by osteoclasts cannot be excluded.…”
Section: Discussionmentioning
confidence: 90%
“…Detailed studies have been carried out on the thermal stability of collagen molecules with altered posttranslational modification patterns due to mutations [19], alterations of the enzymes and cofactors involved [20,211 or excess reactive oxygen [22]. Studies on the thermally induced overmodified collagen I from cell cultures demonstrated that over-glycosylation could decrease the diameter of collagen fibrils formed in vitro [7].…”
Section: Discussionmentioning
confidence: 99%
“…Mycotoxins are indeed known to induce lipid peroxidation, an effect that can be prevented by antioxidants [5,11,12]. In animal experiments, FA and selenium deficiency have been reported to be associated with degeneration of articular cartilage, modification of collagen I in bone and collagen II in cartilage, development of fibrocartilage at the articular surface and impaired formation of subchondral bone [14]. The object of this study was to identify the risk factors for KBD in Tibet and to estimate the relative importance of each factor.…”
Section: Introductionmentioning
confidence: 99%